The Inflammasomes: Molecular Effectors of Host Resistance Against Bacterial, Viral, Parasitic, and Fungal Infections - Skeldon, Alexander; Saleh, Maya (Frontiers in Microbiology, 2011)
The inflammasomes are large multi-protein complexes scaffolded by cytosolic pattern recognition receptors (PRRs) that form an important part of the innate immune system. They are activated following the recognition of microbial-associated molecular patterns (MAMPs) or host-derived danger signals (danger-associated molecular patterns or DAMPs) by PRRs. This recognition results in the recruitment and activation of the pro-inflammatory protease caspase-1, which cleaves its preferred substrates pro-interleukin-1β (IL-1β) and pro-IL-18 into their mature biologically active cytokine forms. Through processing of a number of other cellular substrates, caspase-1 is also required for the release of “alarmins” and the induction and execution of an inflammatory form of cell death termed pyroptosis. A growing spectrum of inflammasomes have been identified in the host defence against a variety of pathogens. Reciprocally, pathogens have evolved effector strategies to antagonize the inflammasome pathway. In this review we discuss recent developments in the understanding of inflammasome-mediated recognition of bacterial, viral, parasitic and fungal infections and the beneficial or detrimental effects of inflammasome signalling in host resistance.